Gateways to Democracy, 4th Edition - John G. Geer; Richard Herrera; Wendy J. Schiller; Jeffrey A. Segal (Cengage Learning, 2019)
Helping you see the relevance of government in your own life, Geer/Herrera/Schiller/Segal's GATEWAYS TO DEMOCRACY, ENHANCED, 4th edition, thoroughly explains how the U.S. political system works, pointing out the "gateways" that facilitate--or even block--participation. The ENHANCED edition provides updates from the 2018 election, coverage of the frustrated electorate and the role of the media, as well as expanded discussion of diversity and participation that reflects the changing U.S. demographic infrastructure. Chapter-opening vignettes spotlight individuals who have successfully blazed their own trail in politics, such as former President Obama. In addition, Supreme Court cases illustrate the constitutional and legal context in which U.S. democracy has evolved, and a Political Analytics feature helps you evaluate the vast amounts of data present in today's political discourse.